Study of Molecular Interactions in Ternary Liquid Systems Through Theoretical Models at 303K - Pavai2*, L. Balu1, P. Vasantharani2; R. Ezhil (Recent Research in Science and Technology, 2010)
The theoretical velocity in ternary mixtures of alkyl acetates with butanol and formamide at 303K have been evaluated by using theoretical models of liquid mixtures such as Nomoto’s relation, Impedance dependence relation, Ideal mixture relation, collision factor theory and Junjie’s method. Ultrasonic velocity of these mixtures has been measured as a function of concentration and the experimental values are compared with theoretical values. U2exp/U2IMR has also been evaluated for non- ideality in the mixtures. The results are explained in terms of intermolecular interactions occurring in these ternary systems.